2023
DOI: 10.1111/ejn.15998
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic‐related pupil activity reflects level of emotionality during motor performance

Abstract: Pupil size covaries with the diffusion rate of the cholinergic and noradrenergic neurons throughout the brain, which are essential to arousal. Recent findings suggest that slow pupil fluctuations during locomotion are an index of sustained activity in cholinergic axons, whereas phasic dilations are related to the activity of noradrenergic axons. Here, we investigated movement induced arousal (i.e., by singing and swaying to music), hypothesising that actively engaging in musical behaviour will provoke stronger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Conversely, acetylcholinesterase inhibitors, which increase extra-synaptic concentrations of ACh, have been linked to increased depression-like symptoms in both controls (Risch et al, 1980), patients with unipolar and bipolar depression (Janowsky et al, 1972) and animal models (Addy et al, 2015). In the current special issue, Vidal et al (2023) provide evidence that cholinergic signalling mechanisms play a unique role in mediating the interaction between affect and motor control. These data provide a demonstration of the importance of cholinergic systems in mediating emotional encoding and suggest that they may be particularly important for allowing central representations of affect or valence to modulate ongoing behavioural output.…”
Section: Expanding the Palette Of Functions Subject To Cholinergic Mo...mentioning
confidence: 89%
“…Conversely, acetylcholinesterase inhibitors, which increase extra-synaptic concentrations of ACh, have been linked to increased depression-like symptoms in both controls (Risch et al, 1980), patients with unipolar and bipolar depression (Janowsky et al, 1972) and animal models (Addy et al, 2015). In the current special issue, Vidal et al (2023) provide evidence that cholinergic signalling mechanisms play a unique role in mediating the interaction between affect and motor control. These data provide a demonstration of the importance of cholinergic systems in mediating emotional encoding and suggest that they may be particularly important for allowing central representations of affect or valence to modulate ongoing behavioural output.…”
Section: Expanding the Palette Of Functions Subject To Cholinergic Mo...mentioning
confidence: 89%
“…Note that the reported pupillary effects for cueassociated uncertainty and vowel-outcome probability do not depend on the chosen preprocessing steps and parameters, as the analysis of non-preprocessed pupil data (without interpolation, filtering, downsampling) leads to an identical pattern of significant effects. Furbased on procedures in previous studies (Montefusco-Siegmund et al, 2022;Vidal et al, 2023) and to test for the robustness of the results, we repeated the final models of cue-associated uncertainty and probability with the pupil data filtered with a band-pass filter of 0.02-1 Hz. This approach led to reduced, but similar effects for uncertainty (main effect of intermediate uncertainty: β = À 13.144, t 7204 = À0.835, P = 0.403; main effect of low uncertainty: β = À 26.146, t 7204 = À1.838, P = 0.066) and equivalent probability effects (main effect of probability: β = À 60.185, t 7089 = À2.1, P = 0.036; main effect of task accuracy: β = À 28.474, t 7089 = À2.375, P = 0.018; main effect of trial: β = À 0.225, t 7089 = À3.227, P = 0.001).…”
Section: Pupil Dilation Response Reflects Differences In Visual Cue-a...mentioning
confidence: 99%
“…On the other hand, cholinergic projections exhibited sustained activation when the pupil was dilated for an extended period, such as during locomotion (Reimer et al, 2016). The relation of acetylcholine and pupil diameter in humans is less clear as several studies using cholinergic manipulation via supplements or induced movement have also found negative scaling of pupil diameter (Naber et al, 2015;Vidal et al, 2023).…”
Section: The Effect Of Cue-associated Irreducible Uncertainty On the ...mentioning
confidence: 99%
“…[13][14][15][16] Greater task-evoked pupil dilations and pupil size have consistently been linked to increased attention 3 allocation since the 1960s [17][18][19][20] and, more recently, oscillatory pupil activity (particularly in the delta range between ~0.5 and 2 Hz) has been demonstrated to entrain to rhythms and appears to be related to movement. [21][22][23] Unlike electroencephalography, the event-related pupil dilation response is so sluggish (typically peaking between ~500-1200 ms post-event onset 24,25 ) that phase-aligned pupil dilations can be interpreted as entrained rather evoked. This is particularly relevant for testing theories like dynamical systems where the difference between evoked and entrained responses is crucial to the underlying neural mechanism.…”
Section: Evoked and Entrained Pupillary Activity While Moving To Pref...mentioning
confidence: 99%